Adopt or not: Manufacturers' RFID decisions for gray marketing in a competitive environment. (January 2021) - Ding, Long; Yuan, Hongping; Hu, Bin
Highlights: We introduce RFID into gray marketing in a competitive environment. We study the interplay between RFID adoption and gray marketing decisions. We examine the impact of competition intensity on manufacturers' profit. We investigate how competition intensity affects gray marketing decisions. Abstract: With the global development of the e-commerce economy, gray marketing has increased sharply and caused significant impacts on manufacturers. Radio frequency identification (RFID) technology provides a new approach for gray marketing management. In this paper, we introduce RFID to track the distribution of products within the gray marketing in a competitive environment. Using a game-theoretical model, we investigate the interplay between the manufacturers' RFID adoption decisions and the third-party's gray marketing decisions and examine the impacts of competitive intensity on firms' profits and decisions. We observe that RFID narrows the scope of the third-party's gray marketing and competitive intensity plays an important role in influencing the third-party's gray marketing decisions. The third-party's gray marketing decisions depend on the RFID double effects (cost effect and punishment effect), market disparity, and competitive intensity. Despite the benefits of RFID, the manufacturer does not always adopt it. When the market disparity is sufficiently small, the manufacturer will not adopt RFID. When the market disparity is sufficiently large, the manufacturer will only adopt RFID if the RFID punishment effect is strong. We also find that increased competitive intensity decreases the third-party's incentive to engage in gray marketing. Finally, although gray marketing decreases the branded manufacturer's profits, it may also increase the competitor manufacturer's profits. Therefore, public policymakers should take into account the positive impacts of gray marketing on competitor manufacturers when they formulate policies to inhibit gray marketing. Public policies should be developed to promote the entire social welfare.